Biogenic amines in some natural and processed cheeses sold in Laguna province, Philippines. - Vallejos, Ma. Jannine M. (Philippine Journal of Science)
Natural and processed cheese samples from the different supermarkets around Laguna Province in the Philippines were analyzed for the presence and quantity of biogenic amines using thin layer chromatography with Biosoft Quantiscan program. The histamine concentrations were 113.4 + 1.8 ppm, 217.9 + 1.0 ppm, and 49.9 + 3.6 ppm in Blue, Cheddar, and Edam Cheese, respectively. The histamine limit in cheese is 100 mg/kg, hence the level found in Cheddar cheese needs to be looked into. The tyramine contents were 2269.3+3.6 ppm, 571.3 + 2.0 ppm and 199.7 ppm in Blue, Cheddar, and Edam cheese, respectively. Because the limit for tyramine in cheese is 200 mg/kg, the levels found in Blue and Cheddar cheese are of serious concern. Brie, processed cheese and white soft cheese (kesong puti) were negative for both histamine and tyramine. All cheeses were negative for cadaverine. High levels of histamine and tyramine found in the cheese samples analyzed indicate the need to expand sampling to other natural cheese varieties sold in the province. Then, actual or anticipated human exposure risk to BAs in cheese can be determined to ascertain the necessity for the Food and Drug Administration and other government agencies concerned with food safety to take action.